2013
DOI: 10.1097/mao.0b013e3182868608
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between a New Implantable Transcutaneous Bone Conductor and Percutaneous Bone-Conduction Hearing Implant

Abstract: The Sophono offers appealing clinical benefits of transcutaneous bone conduction hearing; however, the audiologic challenges of transcutaneous application remain, as the Sophono does not exceed percutaneous application regarding audiologic output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 16 publications
7
90
5
1
Order By: Relevance
“…The study of Hol [11] in children with ear atresia is the only one comparing, the aided ACPTA thresholds and aided SRT with Sophono Alpha1 to those obtained with a BAHA1 on abutment (6 children in each group): the aided ACPTA threshold was 3 dB better (33 vs. 36 dB) and the aided SRT 7 dB better (23 vs. 30 dB) with the percutaneous BAHA1. The auditory results reported here with Sophono Alpha1 in a very similar population (high grade ear atresia) are within the same range, with a mean aided ACPTA of 33.49-36.43 dB (at month 6 and 12), and a mean aided SRT of 38.27 and 39 dB (at month 6 and 12).…”
Section: Discussionmentioning
confidence: 98%
“…The study of Hol [11] in children with ear atresia is the only one comparing, the aided ACPTA thresholds and aided SRT with Sophono Alpha1 to those obtained with a BAHA1 on abutment (6 children in each group): the aided ACPTA threshold was 3 dB better (33 vs. 36 dB) and the aided SRT 7 dB better (23 vs. 30 dB) with the percutaneous BAHA1. The auditory results reported here with Sophono Alpha1 in a very similar population (high grade ear atresia) are within the same range, with a mean aided ACPTA of 33.49-36.43 dB (at month 6 and 12), and a mean aided SRT of 38.27 and 39 dB (at month 6 and 12).…”
Section: Discussionmentioning
confidence: 98%
“…Their results showed significant attenuation (12–23 dB) with the TCBCI between 4 to 8 kHz when the processor was used a signal generator, and also during measurement aided sound field thresholds with the processor used conventionally as a hearing amplifier, although attenuation was less pronounced in the latter condition (smaller by ~3 dB)[3]. Hol et al compared a different TCBCI system (Sophono Alpha 1, Boulder, CO) in 6 patients matched to the same number of subjects implanted with a DCBCI [4]. Similarly to Kurtz et al, their results showed poorer aided and speech reception thresholds in the TCBCI group [4].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the Alpha 1 system has already been described in conductive or mixed hearing loss in adults and children [Denoyelle et al, 2013;Escorihuela-García et al, 2014;Hol et al, 2013;Magliulo et al, 2015;Siegert and Kanderske, 2013;Sylvester et al, 2013;]. No studies have yet been published in the English literature concerning the use of Alpha 2.…”
Section: Discussionmentioning
confidence: 99%
“…The Sophono Alpha system is a bone-conductive transcutaneous implant that transmits the vibrations of the external processor thought an intact skin by means of a magnetic coupling. It was first described by Siegert [2011], and since then other papers have been published concerning the use of this device in different pathological conditions [Denoyelle et al, 2013;Escorihuela-García et al, 2014;Hol et al, 2013;Leterme et al, 2015;Magliulo et al, 2015;Siegert and Kanderske, 2013;Sylvester et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation